PENINGKATAN PENGETAHUAN, KETERAMPILAN DAN SIKAP PARA KAUM MUDA DALAM PERSIAPAN MEMASUKI DUNIA KERJA - Linus Kali Palindangan (Jurnal Bakti Masyarakat Indonesia, 2020)
This training activity was held thanks to the collaboration of the Tarakanita School of Communication Science and Secretariat (STIKS Tarakanita) Jakarta with the Jakarta Marga Sejahtera Non-Governmental Organization. This activity was held to provide knowledge and training for young people from Marga Sejahtera NGOs. The youths from the NGO Marga Sejahtera are all high school and vocational high school graduates who have not yet found work. All of them are then gathered to be given various knowledge, skills, and attitudes which are expected to facilitate and assist them in finding work and work. The method used in this activity is training. While the speakers of this training are Tarakanita STIKS lecturers. There are also results obtained from this training are (1) participants have adequate knowledge about the world of work, (2) participants are skilled in preparing a letter of application and CV, (3) participants are skilled in accessing the information on job opportunities through various media including procedures for applying for jobs in a way online, (4) participants send applications to companies that open job vacancies according to participant specifications, and (5) participants have a good attitude and personal performance. Based on the evaluation of the participants both verbally and in writing at the end of the event, it was concluded that similar activity was highly recommended for job seekers, both a high school / vocational and graduate graduates. Because this activity is considered very helpful for each participant in preparing to get a jobABSTRAK:Kegiatan pelaltihan ini terselenggara berkat kerjasama Sekolah Tinggi Ilmu Komunikasi dan Sekretari Tarakanita (STIKS Tarakanita) Jakarta dengan Lembaga Swadaya Masyarakat Marga Sejahtera Jakarta. Kegiatan ini diselenggarakan untuk memberika pengetahuan dan latihan bagi para pemuda dari LSM Marga Sejahtera. Para pemuda dari LSM Marga Sejahtera semuanya adalah lulusan SMU dan SMK yang belum mendapatkan pekerjaan. Mereka semua kemudian dikumpulkan untuk selanjutnya diberikan berbagai pengetahuan, keterampilan dan sikap yang diharapkan akan memudahkan dan membantu mereka dalam mencari pekerjaan dan bekerja. Metode yang dipakai dalam kegiatan ini adalah pelatihan. Sementara para narasumber pelatihan ini adalah para dosen STIKS Tarakanita. Ada pun hasil yang diperoleh dari pelatihan ini adalah (1) perserta mempunyai pengetahuan yang memadai tentang dunia kerja, (2) peserta terampil menyusun surat lamaran dan CV, (3) peserta terampil mengakses informasi peluang kerja melalui berbagai media termasuk tata cara melamar pekerjaan secara online, (4) peserta mengirim lamaran ke perusahaan yang membuka lowongan pekerjaan sesuai spesifikasi peserta, dan (5) peserta memiliki sikap dan personal performance baik. Berdasarkan evaluasi dari peserta baik secara lisan maupun tertulis diakhir acara, disimpulkan bahwa kegiatan yang serupa sangat direkomendasikan bagi para pencari kerja, baik lulusan SMU/SMK maupun lulusan sarjana. Kegiatan ini dipandang sangat membantu setiap peserta dalam mempersiapkan diri mendapatkan pekerjaan